Family Violence Directed Against the Kindergarten Child and Its Relationship to Some Variables (Journal Of Educational and Psychological Researches, 2023)
The research aims at identifying the level of family violence directed against the kindergarten child, as well as to identify the significance of the difference in family violence directed against the kindergarten child according to the gender variable(male-female). It aims also to identify the significance of the difference in family violence directed against the kindergarten child according to the Stage variable (kindergarten-pre-primary). The researcher employed the descriptive correlative approach to conduct the study. The research sample was chosen in a simple random way, as the number of the participants was (130) boys and girls, with (70) males and (60) females, distributed according to the stage with (66) participants in the preliminary stage and (64) participants in the kindergarten stage, which divided into (8) kindergartens at the Karkh Education Directorates (first, second, third). The researcher also resorted to developing a scale of (15) items to measure the domestic violence directed against kindergarten children. The reliability was verified at (0.84). The results of the research revealed that there is violence against kindergarten children by the family